Exploring the impacts of terminal mutations on the thermostability of Bacillus sp. L2 lipase - Ishak, Siti Nor Hasmah; Mohd Faizal, Khairina Alya; Anasir, Mohd Ishtiaq; Bukhari, Noramirah; Zulkifli Lubis, Nur Aisyah; Mat Radzi, Mohd Radzman; Leow, Adam Thean Chor; Mohamad Ali, Mohd Shukuri; Mohd Shariff, Fairolniza (University of Malaya, 2025)
Protein engineering has been widely used to improve enzyme properties and make them appropriate for use as industrial biocatalysts. To study the effect of mutation at the N-and C-terminal of lipase, two double mutants (A8V/S385E and A8P/S385E) were generated by site-directed mutagenesis of L2 lipase from Bacillus sp. (wt-L2). The simultaneous mutations in the A8V/S385E and A8P/S385E resulted in significant changes in the lipase's properties compared to the wild-type (wt-L2). The mutants demonstrated increased thermostability compared to the wild-type. The melting temperature (Tm) analysis using circular dichroism revealed higher Tm values of 84.5 °C for A8P/S385E and 75.1 °C for A8V/S385E. This indicates that the enzyme can withstand higher temperatures before denaturation, a desirable trait in various industrial processes. Secondary structure analysis indicated alterations in the lipase structure caused by the simultaneous mutations. In summary, the simultaneous mutation at the C-and N-terminals had a multifaceted impact on the lipase, influencing its optimal temperature, thermostability, and structural characteristics. These findings provide insights into how specific genetic modifications can be employed to tailor the enzyme for improved performance in industrial applications.